Unitary space-time codes from Alamouti's scheme with APSK signals. - Aijun Song (IEEE Transactions on wireless communications)
Unitary space-time codes have been used in differential space-time modulation, when neither the transmitter nor the receiver of a multiple antenna system knows the channel state information in Rayleigh fading channels. Among the codes in literature, unitary orthogonal space-time codes, constructed from Alamouti's scheme, have the advantage of fast maximum likelihood (ML) decoding but they require signal constellations to be phase-shift keying (PSK). In this paper, unitary space-time codes are constructed from Alamouti's scheme with amplitude/phase-shift keying (APSK) constellations. We show that the unitary space-time codes from Alamouti's scheme with APSK signals have larger diversity products than those with PSK signals while the complexity of their ML decoding algorithm is comparable. Our newly proposed 4 b/s/Hz code has about 2 dB gain over the same rate code with PSK signals at bit-error rate (BER) of 10-3 with one receive antenna. We also propose a noncoherent scheme of rate 5 b/s/Hz, which has the same BER performance as the 4 b/s/Hz unitary orthogonal space-time code in DSTM while having comparable decoding complexity.